Linnaeus, the essentialism story, and the question of types. Issue 6 (1st October 2020) - Witteveen, Joeri
Abstract: According to an influential twentieth‐century narrative, Linnaeus's taxonomic endeavors rested on a suspect metaphysical basis of "typological thinking" or "essentialism". Since the beginning of this century, historians and philosophers have shown that this narrative is deeply problematic and fails to be supported by the close study of Linnaeus's actual taxonomic principles and practices. Magnus Lidén has recently argued in Taxon that this revisionist literature on Linnaeus nevertheless preserves a residue of unwarranted attributions of typological thinking aimed at Linnaeus. I argue that this is incorrect and contend that Lidén misinterprets the recent literature on the history of "type concepts" in taxonomy, which has nothing to do with typological thinking. With this article, I hope to show that the historiography of taxonomy is helped, not hindered, by enquiring into Linnaeus's use of certain type concepts and his unfamiliarity with others.